Serum Thyroglobulin Determinations in Patients with Differentiated Thyroid Carcinoma - Bednář, J.; Němec, J.; Zamrazil, V.; Váňa, S.; Pohunková, D.; Rohling, S. (Nuklearmedizin - NuclearMedicine, 1983)
Serum thyroglobulin levels were measured in 636 patients with differentiated thyroid carcinoma, in whom altogether 1240 determinations were performed in different phases of disease and treatment. A modified sensitive radioimmunoassay was employed using an own high-specific thyroglobulin antibody. The results showed that both the majority of patients with functioning metastases accumulating radioiodine and with non-functioning metastases which could not be detected by scanning had higher serum TG levels, compared with a group of healthy subjects. However, “normal” TG values in patients with metastases, especially non-functioning, were found too. Thus, these findings decrease the diagnostic value of the TG determination. The highest TG values were found in patients with distant metastases of differentiated thyroid carcinoma (in lungs and bones); on the other hand, the proportion of patients with lymph-node(s) métastasés and “normal” TG levels was relatively high. We suggest that the serum TG determination cannot generally replace scanning with l31I and cannot serve as the only test, while being a helpful indicator in the long-term follow-up of differentiated thyroid cancer patients.